Influence of the "Military Diplomacy" in the Chilean Armed Forces During the Early Cold War 1942-1952 - Garay-Vera, C (UNIV CATOLICA TEMUCO, 2018)
The authors characterize a period of the civil - military relations in Chile previous to the crisis of 1973. It is the period between 1942 and 1952 to apply a concept of "military diplomacy" and to describe the professional autonomous relations between the armed forces of Chile and the United States. This allows us to check Huntington s professionalism model, as even though these contacts between the Armed Forces relate in a professional level, by means of the military American assistance, in the frame of Pan-American cooperation, conformity takes place between the Chilean and the American strategic perspectives. All of this inside a formal subordination in terms of civil - military relations. This allows the Chilean military personnel in charge to communicate, at the level of the political conduction and of the Ministry of Foreign Affairs of Chile, their proposals reconciled with the military commanders.